Analysis of Factors Affecting Human Development Index in the Ex-Resident of Semarang and Surakarta - Sulistiani; Setiartiti , Lilies (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The HDI achievements in the ex-resident of Semarang and Surakarta show high and stable performance. Even though there are 2 regencies, namely Grobogan and Wonogiri, with HDI achievements that contrast with the cities of Salatiga, Semarang and Surakarta, the HDI in each district/city continues to increase every year. This research aims to analyze the effect of Minimum Wage, Economic Growth, Government Expenditure on Education and Health on the Human Development Index (HDI) in the Ex-Resident of Semarang and Surakarta, Central Java Province. The object is in 13 districts/cities in the period 2015-2019. Data were collected from Central Bureau of Statistics (BPS) and Directorate General of Fiscal Balance (DJPK) using panel data regression with random efect as the best model selected. The result is that the Minimum Wage has a significant positive effect on HDI. Economic Growth has no significant effect on HDI caused most people do not actively contribute to increasing economic growth due to unequal income distribution, so not all levels of society can receive the benefits. Government Expenditure on Education has a significant negative effect on HDI caused the increase in the number of students and school infrastructure has not been matched by the quantity and quality of educators. In addition, education is a long-term investment, so this variable in the research period has not shown a positive impact on HDI. Government Expenditure on Health has no significant effect on HDI caused the increasing population is not accompanied by an increase in health facilities.